Numeracy skill development in prospective mathematics teachers: Challenges and opportunities in real-world contexts - Winarni, Sri; Kamid; Marzal, Jefri; Asrial (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Numeracy skills are essential for prospective mathematics teachers as they bridge mathematical concepts with real-life applications. However, many prospective mathematics teachers face challenges in applying these concepts to practical situations. This study aims to analyze the conceptual and procedural errors made by prospective mathematics teachers when solving numeracy problems within the context of